Review of ophthalmology quick text review & MCQ's - Khurana, A. K.; Khurana, Aruj K.; Khurana, Bhawna (Jaypee, The Health Sciences Publisher, 2015)
The supplementary book Review of Ophthalmology is also thoroughly revised and updated with recent advances, new concepts and principles of investigation, treatment, and surgical procedures developed since the previous edition. The second half of the book provides multiple choice questions corresponding to each of the twenty review chapters.